Implementation of regenerative braking on the AC locomotive with a mono phase reversible voltage converter - V. A. Kuchumov; I. N. Nikonchuk (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The authors analyse the problem of implementing regenerative braking on the AC locomotive with a monophase reversible voltage converter.Materials and methods. The article consided theoretically possible options for the operation of monophase reversible voltage converters during regenerative braking, in which: 1) the reactive component of the electric locomotive current had a capacitive nature, and the operating current of the electric locomotive was ahead of its reactive component; 2) the reactive component of the electric locomotive current had an inductive nature, and the current of the electric locomotive was ahead of its active component. The research demonstrated that the former was only theoretically possible, since the regeneration of current into the contact network was carried out at a very low voltage, significantly less than the lowest voltage on the current collector. The latter was technically feasible in terms of the main harmonic of the electric locomotive current lagged by an angle exceeding of 90 electrical degree, but noticeably smaller than 180 electrical degree. Regenerative braking with a power factor close to unity was possible only theoretically, but in practice a power factor of 0.8–0.9 should be realized. The tangent of the angle between the effective current and its active component was greater (for a certain margin) than the quotient from dividing the active by the inductive resistance of the traction network between the electric locomotive and the traction substation. Moreover, it was necessary to consider the technological reduction of the ohmic resistance in the process of the monophase reversible voltage transducer control (e. g. over the deterioration of contact wire).Results. The article demonstrates the possibility and conditions for the regenerative braking implementation on AC locomotives. Hence, a more advanced electric locomotive current control system with an additional channel for regulating the inductive component of the recuperation current is recommended for development.Discussion and conclusion. An advanced control system stabilizes the current collector voltage and with the channel for regulating the active component of the regeneration current provide for the voltage maintanance at a higher level, determined by the actual electrical parameters of the contact network and the train traffic.